Does eco-innovation lift firm value? The contingent role of institutions in emerging markets. Issue 8 (16th August 2019) - Yao, Qiong; Liu, Jinxin; Sheng, Shibin; Fang, Heng
Abstract : Purpose: Drawing on the literature of eco-innovation and institutional theory, this research aims to answer two fundamental questions: Does eco-innovation improve or harm firm value in emerging markets? and How institutional environments moderate the relationship between eco-innovation and firm value? We explicate the regulatory, normative and cognitive pillars of institutions, manifested as regulation intensity, environmental agency pressure and public pressure, respectively. Design/methodology/approach: For this study, a cross-sectional panel data set was assembled from multiple archival sources, including data coded from the corporate annual reports and social responsibility reports, statistical yearbooks, China Stock Market Financial Database (CSMAR) and other secondary sources. A hierarchical regression method was used to test the hypotheses. The data comprised 88 firms sampled over four years. The model using feasible generalized least squares (FGLSs) to control heteroscedasticity in errors due to unobserved heterogeneity was estimated. Findings: Empirical findings from a data set compiled from multiple archival sources reveal that both eco-product and eco-process innovation negatively relate to firm value. The interactions between eco-innovation and regulation intensity, environmental agency pressure and public pressure are positively related to firm value. Originality/value: First, this study extends the literature of eco-innovation by investigating the impact of eco-innovation on firm value. Contrary to the conventional anecdotal evidence of the beneficial effect of eco-innovation, it was found that eco-innovation relates negatively to firm value. Second, this study develops and tests an institutional contingent view of eco-innovation by accounting for the moderating role of regulatory, normative and cognitive pressures.